Cryptocurrency investment intentions of generation Z - Yulfiswandi; Kenrick; Candy (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2026)
This study aims to analyze the influence of financial literacy, perceived risk, facilitating conditions, and social influence on behavioral intention, with attitude as a mediating variable. The sample consisted of 430 Generation Z respondents from Batam City, selected via convenience sampling, and the data were analyzed using Structural Equation Modeling (SEM) in SmartPLS. The results showed that financial literacy and social influence had a significant positive effect on attitude, whereas facilitating conditions had a significant positive effect on attitude but not on behavioral intention, and perceived risk did not significantly influence attitude. Attitude was shown to have a strong positive influence on behavioral intention. Financial literacy and social influence also had an indirect effect on behavioral intention through attitude, while perceived risk did not show a significant mediating effect. This study provides insight into the factors that influence behavioral intention and the important role of attitude as a mediating variable